2023
DOI: 10.1039/d2em00124a
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of oligomer-forming reactions involving the major functional groups present in atmospheric secondary organic aerosol particles

Abstract: Atmospheric organic aerosol particles impact climate as well as human and environmental health. Secondary organic aerosol (SOA), which is formed by the gas-to-particle partitioning of products of the oxidation of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The ROOH decomposition rate may vary significantly, likely owing to the stability and reactivity of the ROOH. Although some studies showed that ROOH can be stable in room temperature for as long as 24 h, , ROOH in atmospheric OA were more often found to be rather labile, especially for the highly functionalized molecules, with the first-order decomposition rate ranging from 3 × 10 –5 s –1 to ∼2 × 10 –3 s –1 . Furthermore, little is known regarding the detailed ROOH decomposition mechanism and products. Unimolecular decomposition via breaking the weak O–O bond to form RO • and • OH was suggested as a possible reaction at ambient temperature for peroxides with O/C ratios at 0.5 or higher .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The ROOH decomposition rate may vary significantly, likely owing to the stability and reactivity of the ROOH. Although some studies showed that ROOH can be stable in room temperature for as long as 24 h, , ROOH in atmospheric OA were more often found to be rather labile, especially for the highly functionalized molecules, with the first-order decomposition rate ranging from 3 × 10 –5 s –1 to ∼2 × 10 –3 s –1 . Furthermore, little is known regarding the detailed ROOH decomposition mechanism and products. Unimolecular decomposition via breaking the weak O–O bond to form RO • and • OH was suggested as a possible reaction at ambient temperature for peroxides with O/C ratios at 0.5 or higher .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The first-stage POA had an average O/C of 0.65 and 0.56 for n -pentane and n -heptane, respectively, and thus falls under OOA, a category previously reserved for SOA ( 4 , 28 , 29 ). Furthermore, ESI-MS spectra show repetitive clusters of peaks separated by 14 u, which is indicative of oligomer formation ( 30 ), another feature usually associated with SOA ( 31 33 ) and is further explored in the subsequent section. It is possible that the first-stage POA included some reduced species that were not detected by ESI-MS, but the fact that it was completely transparent to LDI-MS indicates that reduced species, if any, did not constitute a substantial fraction.…”
Section: Resultsmentioning
confidence: 96%
“…In fact, in a study comparing various accretion reactions between compounds including hydroperoxide, hydroxyl, carboxyl, aldehyde, and ketone functional groups, the reaction of hydroperoxides and aldehydes to form peroxyhemiacetals were the most favorable even without the presence of an acid catalyst. 90 In addition, Hall and Johnston 91 indicated that under low-NO x conditions, because of the dominant fate of RO 2 reacting with HO 2 , hydroperoxides are likely to be formed and further react with aldehydes which subsequently contributes to peroxyhemiacetal production, thereby lowering SOA volatility. The C 11 H 20 O 8–9 structures were only observed in negative mode so they cannot be peroxyhemiacetals.…”
Section: Resultsmentioning
confidence: 99%